2016
DOI: 10.1017/cbo9781139942072
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Control of Wave Energy Devices

Abstract: With this self-contained and comprehensive text, students and researchers will gain a detailed understanding of the fundamental aspects of the hydrodynamic control of wave energy converters. Such control is necessary to maximise energy capture for a given device configuration and plays a major role in efforts to make wave energy economic. Covering a wide range of disciplines, the reader is taken from the mathematical and technical fundamentals, through the main pillars of wave energy hydrodynamic control, righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 88 publications
2
84
0
6
Order By: Relevance
“…2) Test 2: The resulting parameter adaptation due to the doubling of the hydrodynamic radiation force in the linear simulation is illustrated in Fig 9-(a), which plots the evolution of the first three diagonal parameter values of the N matrix. Fig 9-(a) shows that the parameters N(1, 1), N(2, 2) and N (3,3), which relate to the hydrodynamic radiation, converge to values approximately double their initial values, as might be expected. The effect of the adaptation of all the parameters in the N matrix is demonstrated in Fig 9-(b), which plots the actual simulated radiation force over a control horizon, and the linear control model approximation to this at the 15 collocation points, for both the initial and the adapted control models.…”
Section: ) Testsupporting
confidence: 65%
See 2 more Smart Citations
“…2) Test 2: The resulting parameter adaptation due to the doubling of the hydrodynamic radiation force in the linear simulation is illustrated in Fig 9-(a), which plots the evolution of the first three diagonal parameter values of the N matrix. Fig 9-(a) shows that the parameters N(1, 1), N(2, 2) and N (3,3), which relate to the hydrodynamic radiation, converge to values approximately double their initial values, as might be expected. The effect of the adaptation of all the parameters in the N matrix is demonstrated in Fig 9-(b), which plots the actual simulated radiation force over a control horizon, and the linear control model approximation to this at the 15 collocation points, for both the initial and the adapted control models.…”
Section: ) Testsupporting
confidence: 65%
“…This is consistent with the findings in [18], where both the radiation and added mass values identified from CFD NWT experiments were seen to increase relative to those identified from BEM data. The evolution of N (2,9), N(2, 10) and N (3,10) are also plotted in Fig. 8, showing an increase in the parameter values identified from the CFD simulation, and little change to those identified from the linear simulation.…”
Section: ) Testmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have shown that one of the key aspects for maximizing the energy yield of many WECs is the control of the dynamic response of the device to wave conditions, also defined as hydrodynamic control [1]. More precisely, we consider here the response control of the WEC captor, or primary converter, whose task is to transfer energy from wave to oscillating body, via the power-take off (PTO) system, responsible of a further energy conversion, generally to electricity.…”
Section: Introductionmentioning
confidence: 99%
“…1 which provides a simplified representation of a heaving-buoy wave energy converter). The reader can refer to [1] for an extended definition of primary and secondary converters. Latching control, model predictive control (MPC) and PID control are examples of implementable WEC control strategies [2].…”
Section: Introductionmentioning
confidence: 99%